2021
DOI: 10.1002/apj.2708
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics simulation of multi‐phase flow characteristics in an industrial‐scale randomly packed tower

Abstract: A three-dimensional (3-D) two-phase Eulerian-Eulerian-based computational fluid dynamics (CFD) simulation method coupled with a porous media model was developed in this study to simulate the air-water two-phase flow in an industrial-scale randomly packed air cooling tower (RPACT). The authors discussed the effects of gas kinetic energy factor, liquid load, packing materials, and packed bed height on the hydrodynamic performances of the gas-liquid counter-current flow in the proposed RPACT. The simulation resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In the literature, there is an extensive number of experimental and numerical studies on structured packings. Most of them focus mainly on characterizing and predicting the gasliquid interfacial area for mass transfer in structured packings [4,[6][7][8][9][10][11], including the pressure drop evaluation [12][13][14][15][16][17][18], the amount of liquid holdup [19][20][21][22], and liquid phase dispersion in the packing columns [23][24][25][26]. A review of CFD simulations of structured packings can be found in [27].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there is an extensive number of experimental and numerical studies on structured packings. Most of them focus mainly on characterizing and predicting the gasliquid interfacial area for mass transfer in structured packings [4,[6][7][8][9][10][11], including the pressure drop evaluation [12][13][14][15][16][17][18], the amount of liquid holdup [19][20][21][22], and liquid phase dispersion in the packing columns [23][24][25][26]. A review of CFD simulations of structured packings can be found in [27].…”
Section: Introductionmentioning
confidence: 99%